Mechanisms for the Holton‐Tan relationship and its decadal variation. Issue 6 (18th March 2014) - Lu, Hua; Bracegirdle, Thomas J.; Phillips, Tony; Bushell, Andrew; Gray, Lesley
Abstract This study provides a mechanistic explanation of why the Holton‐Tan (HT) effect, a phenomenon in which the strength of northern stratospheric winter polar vortex synchronizes with the equatorial quasi‐biennial oscillation (QBO), was disrupted in the middle to late winters of 1978–1997. In line with recent reassessments of the HT effect, we find that an easterly QBO in the lower stratosphere leads to the formation of a midlatitude wave guide that enhances both the upward propagating planetary waves from the troposphere into the lower stratosphere ( 35–50°N, 30–200 hPa) and the northward wave propagation in the upper to middle stratosphere ( 35–60°N, 20–5 hPa). This enhanced poleward refraction of planetary waves results in a more disturbed polar vortex, causing the HT effect. The weakening of the HT effect in 1978–1997 was associated with a broader and strengthened polar vortex in November to January. The divergence of wave activity generated by eddies growing within the vortex provided the momentum source and allowed wave activity to propagate meridionally away from the vortex; this interfered with the QBO modulation of planetary wave propagation and led to a weakening of the HT effect during this period. The stronger than average polar vortex in 1978–1997 was associated with a vertically coherent cooling signature over northeastern Asia in the stratosphere. We suggest that a change of stratospheric circulation and/or a change of the stratosphere‐troposphere coupling were the main causes for the disrupted HT effect in 1978–1997.